Reviewer Acknowledgements: Bridging Science, Care, and Community – GHMJ (Global Health Management Journal), Volume 8, Number 2, 2025 - GHMJ (Global Health Management Journal) (GHMJ (Global Health Management Journal), 2025)
As the GHMJ (Global Health Management Journal) continues to advance integrated solutions for global health challenges, this edition highlights cutting-edge research and innovations spanning from molecular science to health systems strengthening. This issue of the Global Health Management Journal (Vol. 8, No. 2, 2025) presents an interconnected range of studies that reflect the dynamic challenges and innovations in global health. Beginning with clinical and pharmacological research, the issue highlights a study on radiographic patterns in tuberculosis patients with and without diabetes (Fatihah et al., 2025)—a dual burden increasingly relevant in both endemic and developing contexts. This clinical insight is followed by two experimental studies on plant-based therapies: one evaluating the hypoglycemic effect of bay leaf and celery extract in diabetic rats (Laorenz et al., 2025), and another investigating the antiviral potential of cassava leaf-derived nicotiflorin against dengue virus serotype 1 (Yulianti et al., 2025), reflecting a growing interest in local bioresources as alternatives to conventional treatment.